2023
DOI: 10.1111/acer.15096
|View full text |Cite
|
Sign up to set email alerts
|

Delayed cortical thinning in children and adolescents with prenatal alcohol exposure

Abstract: Background Prenatal alcohol exposure (PAE) is associated with abnormalities in cortical structure and maturation, including cortical thickness (CT), cortical volume, and surface area. This study provides a longitudinal context for the developmental trajectory and timing of abnormal cortical maturation in PAE. Methods We studied 35 children with PAE and 30 nonexposed typically developing children (Comparisons), aged 8–17 at enrollment, who were recruited from the University of Minnesota FASD Program. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Notably, our finding of higher tCho in PAE groups contrasts with prior evidence that showed lower tCho in older children and adolescents with PAE. This may point to altered developmental trajectories of phospholipid metabolism, myelination, and cortical development in PAE, consistent with findings from structural brain imaging studies (Gimbel et al, 2023; Kar et al, 2022). In fact, no differences in tCho were found in an MRS study of neonates with PAE (Howells et al, 2016), suggesting that alterations in tCho may emerge later in postnatal development and change over childhood.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Notably, our finding of higher tCho in PAE groups contrasts with prior evidence that showed lower tCho in older children and adolescents with PAE. This may point to altered developmental trajectories of phospholipid metabolism, myelination, and cortical development in PAE, consistent with findings from structural brain imaging studies (Gimbel et al, 2023; Kar et al, 2022). In fact, no differences in tCho were found in an MRS study of neonates with PAE (Howells et al, 2016), suggesting that alterations in tCho may emerge later in postnatal development and change over childhood.…”
Section: Discussionsupporting
confidence: 80%
“…These behavioral difficulties emerge in the context of PAE-related brain differences (Donald et al, 2015; Lebel et al, 2011; Moore & Xia, 2022). Reduced white matter and gray matter volume (Nardelli et al, 2011; Subramoney et al, 2022), altered microstructure and developmental trajectories (Donald et al, 2024; Gimbel et al, 2023; Kar et al, 2021, 2022; M. Long et al, 2024; X. Long & Lebel, 2022), and disrupted structural and functional connectivity (X.…”
Section: Introductionmentioning
confidence: 99%
“…Another area with large differences between male and female children with PAE was the right lingual gyrus, which was 16.6% larger in males. Previous research has indicated that the right lingual gyrus shows altered development of cortical structure, such as cortical thinning ( Gimbel et al, 2023 ) in individuals with PAE as compared to an unexposed group. While we are not aware of any other studies that have specifically examined sex effects on development of the right lingual gyrus, it may be that male and female children are differentially susceptible to the insult of PAE, manifesting in stark differences in gray matter regions that are prominently affected by PAE.…”
Section: Discussionmentioning
confidence: 99%
“…HEU children may therefore be demonstrating delayed cortical maturation or disrupted pruning or myelination at this early age. While the clinical significance of this remains to be determined, studies have found profiles of delayed cortical maturation may be associated with mood disorders [57], attention-deficit/ hyperactivity disorder [58], and autism spectrum disorders [59], as well as being linked to other exposures including alcohol [60,61] and infections such as cytomegalovirus infection (CMV) [62]. The process of cortical maturation is dynamic and there is substantial regional heterogeneity in the cortical thickness trajectory.…”
Section: Discussionmentioning
confidence: 99%